Bimodal bilingualism: Language and cognition. Issue 2 (29th February 2016) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
Abstract : Bimodal bilingualism refers to a type of bilingualism that employs two different input-output channels, one involving spoken language and the other involving sign language. Until the second half of the twentieth century, sign language was not recognized as a fully-fledged language and there was very little research devoted to bilingual sign language speakers (Grosjean, 1992 ). In the last two decades, however, interest in the study of bimodal bilingualism, including the cognitive effects of bimodal bilingualism and the neural organization of spoken and sign languages, has increased considerably. Furthermore, the particular significance of studies of bimodal bilingualism for understanding bilingual language representation and processing more generally has been properly recognized. Bilingualism: Language and Cognition has not been silent or inactive on this front. Two years ago we specifically added the study of bimodal bilingualism to the journal's core areas of interest, and we are glad to see an increased number of research articles on bimodal bilingualism (e.g., Giezen & Emmorey, 2016; Rinaldi & Caselli, 2014 ; Williams & Newman, 2015 ; Morford et al., in press; Kaufmann & Philipp, in press).